Creators of worlds: the deposition of R. Gamliel and the invention of Yavneh - Simon-Shoshan, Moshe (AJS review, 2017)
This article will examine the development of Yavneh as a literary and cultural construct from tannaitic sources through the two versions of the story of the deposition of R. Gamliel, in Yerushalmi Berakhot 4:1 and Bavli Berakhot 27b–28a. It will explore the ways in which the talmudic storytellers present a more developed narrative world complete with a social and political culture. It will then analyze the complex relationships between the narrative worlds of the Yerushalmi and Bavli and their respective social and ideological contexts. Based on this analysis, I shall propose a model for understanding the way in which the Yavnehs of both the Bavli and the Yerushalmi functioned in amoraic and postamoraic society to create a nuanced and self-critical rabbinic cultural identity.